Design and fabrication of moving multi-target platform for range training - Tan, Da Neng. (2011)
This design project aims to look into creating a new class of firearms target training platform that is catered specifically for simulating hostage rescue scenarios, which law enforcement officers may face in their line of duty. The underlying motivation behind this initiative is in part due to the heightened security demands observed after the post 9-11 period, where the operation landscape are largely characterized by terrorism and unconventional threats, which current target platform are inadequate in training for. Initial phase of the project first focused on defining the design requirements. This involved studying of the shortcomings of existing design and understanding the user needs. A Conceptual and Detailed design process was then carried out. This can be divided into 3 main areas of focus, namely; (1)Structure, (2)Mechanism and (3)Circuitry and software. Application suitability of the various feasible mechanism designs and actuating system were modeled and simulated using Solidworks solidmotion to analyze their motion. During this process, designs were iterated for a period of about three weeks. As the project progress, it has evolved more towards the creation of an interactive prototype that can react “intelligently” to the shooters, just like an actual terrorist will react in an actual hostage scenario. Finally, in the Prototyping stage, a scale functional model was constructed as a proof-of-concept to test out the design in an actual test shoot. Testing and evaluation was also carried out to identify the areas of improvement of the design concept.